International disputes: case histories 1945-1970 - Donelan, Michael D.; Grieve, M. J. (London, Europa for the David Davies Memorial Institute of International Studies, 1973)
Disputed areas and territories for various countries discussed.
Includes bibliographical references and index.
commitment to retain
Keywords: 1945-1989; World politics -- 1945-1989.; Politique mondiale -- 1945-1989.; World politics; World politics -- 1945-1989.; International relations -- Case studies; 2; International disputes, 1945-1970; Case studies